Facile fabrication of flowerlike natural nanotube/layered double hydroxide composites as effective carrier for lysozyme immobilization - Wang, Y.; Liu, C.; Zhang, Y.; Zhang, B.; Liu, Jian (American Chemical Society, 2015)
© 2015 American Chemical Society. Carrier-based immobilization has been developed to enhance enzymatic stability and activity, which permits the employment of enzymes in different solvents, at wide ranges of pH and temperature as well as high substrate concentrations. In this study, a novel carrier was prepared with halloysite nanotubes (HNTs) and layered double hydroxide (LDH) via a layer-by-layer (LbL) deposition process followed by an in situ growth technique. The in situ growth of LDH nanoplatelets on a HNTs support was demonstrated producing a well-defined three-dimensional architecture (HNTs@LDH). These flowerlike structural materials possess a high lysozyme immobilized amount (237.6 mg/g support) compared with individual HNTs and LDH. And such lysozyme immobilized composites (HNT@LDH-Ly) exhibit a superior antibacterial property against Escherichia coli (E. coli).